Occurrence and habitat association of Hippocampus kuda Bleeker, 1852 in the artificial waterways of Kuwait, northwestern Arabian Gulf - Nithyanandandan, Manickam; Al-Yaqout, Amani; Murugan, Arumugam; Saheb, Azad Ismail; Jayasimhan, Praveenraj; Nallathambi, Moulitharan; Al-Yamani, Faiza (Zootaxa, 2026)
Seahorses occurring in the Arabian Gulf remain incompletely documented despite extensive coastal modification and extreme physicochemical conditions. The yellow seahorse, Hippocampus kuda Bleeker, 1852, has recently been genetically confirmed from Kuwaiti waters, establishing species identity in the region (Bishop et al. 2024). However, specimen-linked records integrating habitat context, morphology, and archived genetic reference sequences remain limited for engineered coastal systems. Opportunistic underwater visual surveys conducted between 2012 and 2015 within the artificial waterways of Sabah Al-Ahmad Sea City (SAASC), Al-Khiran, southern Kuwait, documented three H. kuda individuals in naturally colonized shallow subtidal seagrass meadows at approximately 3 m depth. Individuals were observed clinging to leaf blades in a meadow dominated by Halodule uninervis with small patches of Halophila ovalis at 28°39’3.59"N, 48°22’55.74"E. Salinity was recorded in situ using a YSI 556 Multi-Probe System, and specimens were photographed alive prior to preservation. Morphometric and meristic data are presented for vouchered specimens, including ring counts, fin-ray counts, species-level indices, and proportional measurements (Tables 1–2). Partial cytochrome oxidase subunit I (COI) sequences are reported as archival genetic references linked to documented individuals and habitat observations rather than as analytical evidence (Supplementary File 1). This contribution documents the occurrence and habitat association of H. kuda within seagrass colonising an engineered coastal environment of the northwestern Arabian Gulf.